2011
DOI: 10.1126/scisignal.2002179
|View full text |Cite
|
Sign up to set email alerts
|

Human Regulatory T Cells Rapidly Suppress T Cell Receptor–Induced Ca 2+ , NF-κB, and NFAT Signaling in Conventional T Cells

Abstract: † CD4 + CD25 hi Foxp3 + regulatory T cells (T regs ) are critical mediators of self-tolerance, which is crucial for the prevention of autoimmune disease, but T regs can also inhibit antitumor immunity. T regs inhibit the proliferation of CD4 + CD25 − conventional T cells (T cons ), as well as the ability of these cells to produce effector cytokines; however, the molecular mechanism of suppression remains unclear. Here, we showed that human T regs rapidly suppressed the release of calcium ions (Ca 2+ ) from int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 56 publications
8
69
3
1
Order By: Relevance
“…Our data show that normal human Tregs rapidly reduced TCR-triggered Ca 2+ signaling and activation of NFAT in Tcons, thereby prompting the inhibition of Tcon immune activity, as reflected by substantially diminished IL-2 and IFN-g release and dampened proliferation. These findings are well in line with the results of a recent study that used cocultured, purified T cell populations instead of single cells to demonstrate rapid suppression of Tcon Ca 2+ signaling by Tregs, followed by downregulation of NFAT1 and NF-kB (11). The fast kinetics of cytokine suppression observed in our study is also consistent with the results of a previous study showing that Tregs inhibit the induction of Th1 cytokine mRNA in Tcons as early as 1 h after TCR activation (14).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data show that normal human Tregs rapidly reduced TCR-triggered Ca 2+ signaling and activation of NFAT in Tcons, thereby prompting the inhibition of Tcon immune activity, as reflected by substantially diminished IL-2 and IFN-g release and dampened proliferation. These findings are well in line with the results of a recent study that used cocultured, purified T cell populations instead of single cells to demonstrate rapid suppression of Tcon Ca 2+ signaling by Tregs, followed by downregulation of NFAT1 and NF-kB (11). The fast kinetics of cytokine suppression observed in our study is also consistent with the results of a previous study showing that Tregs inhibit the induction of Th1 cytokine mRNA in Tcons as early as 1 h after TCR activation (14).…”
Section: Discussionsupporting
confidence: 89%
“…Notably, the defective Treg state is ameliorated under disease-modifying treatment, indicating that pharmacological modulation of Tregs might prove to be a promising strategy for restoring immunological homeostasis in MS (7,9,10). Although the molecular mechanisms that confer inhibition and reconstitution have been poorly understood, insights from an elegant, recently published study have provided compelling evidence that Tregs counteract the sustained elevation of intracellular free Ca 2+ ions in target cells and thus interfere with a fundamental requirement for almost all aspects of Tcon activation (11). In that study, cocultured cell populations were used to demonstrate rapid suppression of Tcon Ca 2+ signaling by Tregs, followed by downregulation of the Ca 2+ -dependent transcription factor NFAT1 and NF-kB as important downstream events.…”
mentioning
confidence: 99%
“…T Cell Proliferation Assay-T cell proliferation was measured by [ 3 H]thymidine incorporation as described previously (19). Data were statistically analyzed with the two-tailed unpaired t test with Welch's correction (**, p Ͻ 0.01; ****, p Ͻ 0.0001).…”
Section: Methodsmentioning
confidence: 99%
“…NF-κB is a protein that is ubiquitously expressed in nearly all cell types. 29) Cyclosporine is able to interfere with IκB degradation which might diminish the transcriptional activity of classical NF-κB signalling. Nishiyama et al reported that the presence of cyclosporine could prevent NF-κB from migrating into the nucleus and instead retains it in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%